EFL Students’ Responses on Teacher’s Online Written Feedback: Interaction, Revision, and Perception - Suci, Dewi Nur; Basthomi, Yazid; Mukminatien, Nur; Santihastuti, Asih; Syamdianita, Syamdianita (Indonesian Journal of Applied Linguistics, 2021)
This study examines studentsâ€™ interactions with the teacherâ€™s feedback in an online course on paragraph writing at higher education in Indonesia. The instructional moves, interactional approach, and studentsâ€™ perceived usefulness of the feedback were investigated. Through a discourse analysis framework, 355 comments on discussion posts from five students in four meetings were analyzed. The Learning Analytics (LA) data correlated with semi-structured interviews were employed to obtain the studentsâ€™ perceived usefulness of teacher feedback for revision. The semi-structured interview was done with six students. The findings revealed that the teacher enacted fifteen moves to handle social interaction in online feedback from directive to dialogic categories. These moves are employed to create knowledge-building and solidarity for pedagogical and interactional goals, particularly. These are shown by the relation between LA and the studentsâ€™ perceptions of the feedback for writing revision. Therefore, such ï¬ndings highlight the (de)merits of directive-dialogic interactions in online written feedback and LA data to improve teaching and learning.